Data from: Seasonally dependent relationship between insect herbivores and host plant density in Jatropha nana, a tropical perennial herb - Nerlekar, Ashish N. (Dryad, 2018)
The fact that plant spatial aggregation patterns shape insect herbivore
communities in a variety of ways has resulted in a large body of
literature on the subject. The landmark resource concentration hypothesis
predicts that density of insect-herbivores per plant will increase as host
plant density increases. I examined this prediction across temporal
samplings using Jatropha nana and the associated specialist
insect-herbivores as a system. Through 12 field samplings, I modelled the
effect of host plant density on insect-herbivore loads. The initial
samplings (2-3) provided evidence for the resource concentration
hypothesis with insect loads increasing with increasing host plant
density, whereas the later samplings (4-5, 7-11) showed the opposite- a
resource dilution pattern with decline of insect loads with increasing
host plant density. These patterns also depend on the biology of the
herbivores and have important implications on J. nana population dynamics.
data for Dryad Nerlekar 2018 RCH paperSheet 1 contains the predictor and
response variables re-arranged and results for Poisson regression
analysis. Sheet 2 contains raw data for ramet density, insect load and
relative abundance of each species over samplings.
Keywords: resource concentration hypothesis; resource dilution; Jatropha nana